Exploratory investigation of a patient‐informed low‐dose psilocybin pulse regimen in the suppression of cluster headache: Results from a randomized, double‐blind, placebo‐controlled trial. Issue 10 (23rd November 2022) - Schindler, Emmanuelle A. D.; Sewell, R. Andrew; Gottschalk, Christopher H.; Luddy, Christina; Flynn, L. Taylor; Zhu, Yutong; Lindsey, Hayley; Pittman, Brian P.; Cozzi, Nicholas V.; D'Souza, Deepak C.
Abstract: Objective: Using a patient‐informed regimen, we conducted an exploratory randomized, double‐blind, placebo‐controlled study to systematically investigate the effects of psilocybin in cluster headache. Background: Sustained reductions in cluster headache burden after limited quantities of psilocybin‐containing mushrooms are anecdotally reported, although to date there are no controlled studies investigating these effects. Methods: Participants were randomized to receive psilocybin (0.143 mg/kg) or placebo (microcrystalline cellulose) in a pulse of three doses, each ~5 days apart. Participants maintained headache diaries starting 2 weeks before and continuing through 8 weeks after the first drug session. A total of 16 participants were randomized to receive experimental drug and 14 were included in the final analysis. Results: In the 3 weeks after the start of the pulse regimen, the change in cluster attack frequency was 0.03 (95% confidence interval [CI] −2.6 to 2.6) attacks/week with placebo (baseline 8.9 [95% CI 3.8 to 14.0]) and −3.2 (95% CI −8.3 to 1.9) attacks/week with psilocybin (baseline 9.6 [95% CI 5.6 to 13.6]; p  = 0.251). Group difference in change from baseline had a moderate effect size ( d  = 0.69). The effect size was small in episodic participants ( d  = 0.35) but large in chronic participants ( d  = 1.25), which remained over the entire 8‐week period measured ( d  = 0.81). Changes in cluster attack frequency were not correlated with the intensity of acute psychotropic effects during psilocybin administration. Psilocybin was well‐tolerated without any unexpected or serious adverse events. Conclusions: Findings from this initial, exploratory study provide valuable information for the development of larger, more definitive studies. Efficacy outcomes were negative, owing in part to the small number of participants. The separation of acute psychotropic effects and lasting therapeutic effects underscores the need for further investigation into the mechanism(s) of action of psilocybin in headache disorders.